Chāndogya Upaniṣad: Pengetahuan Esensial Dari Veda - Ni Made Sumaryani; Ni Wayan Sri Rahayu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Vedo ‘khilo dharma mūlam… or the entire Vedic literature is the first/foremost source of dharma…. The Vedas are sacred teachings revealed by God through mahaṛsi. In the beginning, Vedic teaching was carried out based on the Parampara (disciplinary line) through the oral tradition passed down from generation to generation to siyanya. Hinduism has inherited many sacred texts that are truly glorious, the Upaniṣads are one of those sacred libraries in which there are teachings about Brahman and Ātman. The main object of this literature is an investigation into ultimate reality which reaches a step where it is wise and mature enough to cut itself off from all karma. The study of the Chāndogya Upaniṣad is essential as an early warning to humans that all pleasures and sufferings in the world are impermanent. Therefore, the Chāndogya Upaniṣad as one of the Upaniṣads describes the suffering felt by a person who is in a strange place (birth), he really hopes to return to his place of origin (Brahman). The human body is a luxury but worthless without the existence of ātman. The presence of ātman gives value to the body. When ātman is enveloped in worldly qualities, he will provide for the temporary needs of the body, he will work hard to eat and live.